O uso da perífrase modal "tener que+infinitivo" no condicional no discurso digital escrito em espanhol - Costa, Léa Angeline da (2023)
From the perspective of pragmalinguistic analysis, as proposed by Fuentes Rodríguez (2017), this research aims to analyze and describe the deontic modal periphrasis “tener que+infinitive” in digital discourse in the conditional form and its interrelation among the levels of Superstructure, Macrostructure and Microstructure, considering the context. According to Fuentes Rodríguez (2017), pragmalinguistics involves analyzing the text as a global unit and comprehending the elements that compose it in all planes that arise from the interrelation between the levels and environment of the language in use. In the language in use, the periphrasis “tener que+infinitive” is related to the deontic modality, which, according to Gómez Torrego (2016), is defined in essence with the meaning of obligation and lies on the pillar of legal, moral, and social conduct dictated by the state of affairs (ALMEIDA, 1988; NEVES, 1996). However, by observing the conjugation of modal periphrasis in opinions expressed on social media, we questioned ourselves about its pragmalinguistic behavior and the scaling of values in its deonticity, which could occur when conjugated in the conditional form. For this analysis, we used a linguistic material from the Corpus Macrosintaxis del Español Actual - MEsA, collected from the cybergenres, such as Facebook, Twitter, and Instagram, where we found 100 (one hundred) occurrences of “tener que+infinitive” in conditional. In the analyzed data, based on a qualitative and quantitative approach using the Statistical Package for Social Sciences (SPSS), we concluded that cybergender-speaking users more often chose Instagram to establish an obligation through conditional periphrasis in expository sequences with simple sentences and marked structures. In most cases, users have established themselves, predominantly, as a modal source of Speaker-Enunciator-Speaker type in order to impute an obligation to a deontic target in the 3rd-person singular. This periphrasis is generally achieved by a temporal notion oriented towards the future, and is used in contexts that are mostly discourteous, as we assume. Furthermore, we verified the interrelation between all levels and plans that perform in a multidimensional manner in the expression of this modal periphrasis in Spanish used in digital speech.